Synthesis, Characterization and Biological Evaluation of Cu-Ni Bimetallic Nanoparticles - Rasheed, Muhammad Hamza; Taaj , Shaista; Gilani, Ezaz (Journal of Basic and Emerging Sciences, 2024)
A novel green method in which Tulsi is used as a precursor. Cu-Ni bimetallic nanoparticles are obtained by mixing solutions related to metal salts with plant extracts. The plant extracts contain various photochemical contents reducing and capping agents towards the metal ions in the solution. The synthesized particle showed UV absorption of 0.085 and 0.347 at 368 and 206nm, respectively. The FTIR spectrum of Copper-nickel bimetallic nanoparticles was noticeable in the 400-4000 cm range. The widespread peaks are seen sort of 817cm−1which forecast the existence of the ꞊C-H group on the surface of NP. Particles not shown any zone of inhibition against Staphylococcus(+) and E-coli(-).